REPRESENTASI PENDIDIKAN KARAKTER DALAM DAKWAH ISLAM DI MEDIA SOSIAL - Abdi Wael; Hasanudin Tinggapy; Abdul Rasyid Rumata; A. Yusdianti Tenriawali; Ibnu Hajar; M Chairul Basrun Umanailo (Academy of Education Journal, 2021)
This study aims to determine how the representation of the value of character education in Islamic preaching on social media. This research is a qualitative descriptive study. The population in this study were videos of Islamic da'wah on YouTube social media. Data collection techniques in this study used documentation techniques and note-taking techniques. The data that has been collected is then analyzed based on representation theory to describe the representation of the value of character education contained in Islamic da'wah videos on Youtube social media. The results showed that the preaching of Islam on social media, especially Youtube, represented the value of character education in the form of honesty, tolerance, discipline, hard work, independence, love for the country, friendship, and responsibility. These themes are in accordance with the elements of character education formulated by Kemendiknas in 2010. The representation of the value of character education in Islamic preaching on social media can be used as a medium for teaching character education in schools.